EPHA5 mediates trastuzumab resistance in HER2‐positive breast cancers through regulating cancer stem cell‐like properties. Issue 4 (8th January 2019) - Li, Yongfei; Chu, Jiahui; Feng, Wanting; Yang, Mengzhu; Zhang, Yanhong; Zhang, Yanqiu; Qin, Ye; Xu, Juan; Li, Jun; Vasilatos, Shauna N.; Fu, Ziyi; Huang, Yi; et al.
ABSTRACT: Trastuzumab is a successful, rationally designed therapy that provides significant clinical benefit for human epidermal growth factor receptor‐2 (HER2)‐positive breast cancer patients. However, about half of individuals with HER2‐positive breast cancer do not respond to trastuzumab treatment because of various resistance mechanisms, including but not limited to: 1 ) shedding of the HER2 extracellular domain, 2 ) steric hindrance ( e.g ., MUC4 and MUC1), 3 ) parallel pathway activation (this is the general mechanism cited in the quote above), 4 ) perturbation of downstream signaling events ( e.g ., PTEN loss or PIK3CA mutation), and 5 ) immunologic mechanisms (such as FcR polymorphisms). EPHA5, a receptor tyrosine kinase, has been demonstrated to act as an anticancer agent in several cancer cell types. In this study, deletion of EPHA5 can significantly increase the resistance of HER2‐positive breast cancer patients to trastuzumab. To investigate how EPHA5 deficiency induces trastuzumab resistance, clustered regularly interspaced short palindromic repeat technology was used to create EPHA5‐deficient variants of breast cancer cells. EPHA5 deficiency effectively increases breast cancer stem cell (BCSC)‐like properties, including NANOG, CD133+, E‐cadherin expression, and the CD44 + /CD24 −/low phenotype, concomitantly enhancing mammosphere‐forming ability. EPHA5 deficiency also caused significant aggrandized tumor malignancy in trastuzumab‐sensitive xenografts, coinciding with the up‐regulation of BCSC‐related markers and intracellular Notch1 and PTEN/AKT signaling pathway activation. These findings highlight that EPHA5 is a potential prognostic marker for the activity of Notch1 and better sensitivity to trastuzumab in HER2‐positive breast cancer. Moreover, patients with HER2‐positive breast cancers expressing high Notch1 activation and low EPHA5 expression could be the best candidates for anti‐Notch1 therapy.—Li, Y., Chu, J., Feng, W., Yang, M., Zhang, Y., Zhang, Y., Qin, Y., Xu, J., Li, J., Vasilatos, S. N., Fu, Z., Huang, Y., Yin, Y. EPHA5 mediates trastuzumab resistance in HER2‐positive breast cancers through regulating cancer stem cell–like properties. FASEB J. 33, 4851–4865 (2019). www.fasebj.org